Penilaian Prestasi Kerja Pendidik dan Tenaga Kependidikan di MTs Negeri 2 Jember - Rofiq Hidayat; Ninin Anggraeni; Labib Hanif Dzakiri; Atiyatul Wafiroh Elkamila (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The aim of this research is to evaluate the performance of educators and education staff at MTS Negeri 2 Jember using the interview method. Performance evaluation is an important aspect in measuring the performance of educators and education personnel in order to improve the quality of education and the effectiveness of school management. This research uses interview techniques to collect direct data from stakeholders regarding their perceptions of the evaluation system implemented, challenges faced, and suggestions for improvement. The findings show that even though the evaluation was carried out formally, there are several aspects that still require improvement, such as communication, consistency of implementation, and understanding of evaluation metrics. Therefore, better research is needed, dissemination of evaluation criteria, and a more collaborative evaluation approach.